2000
DOI: 10.1046/j.1440-1622.2000.01740.x
|View full text |Cite
|
Sign up to set email alerts
|

A Protocol of Early Spiral Computed Tomography for the Detection of Stones in Patients With Renal Colic Has Reduced the Time to Diagnosis and Overall Management Costs

Abstract: The implementation of a protocol of early spiral CT for patients with suspected renal colic has led to earlier definitive diagnosis and shorter hospital stays. This is associated with a significant reduction in costs associated with managing this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Other investigators have demonstrated the average total diagnostic imaging costs for CT scanning are comparable to other modalities (9,10). Patients undergoing helical CT scanning to investigate suspected nephrolithiasis also spend significantly less total time in the ED (291 vs. 410 min, respectively), and the time to definitive diagnosis is significantly shorter (6.3 vs. 16.8 h, respectively) (11,12). The only disadvantage to helical CT scanning is the two-to threefold larger radiation dose compared with the 3-film IVP (8,9,13).…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have demonstrated the average total diagnostic imaging costs for CT scanning are comparable to other modalities (9,10). Patients undergoing helical CT scanning to investigate suspected nephrolithiasis also spend significantly less total time in the ED (291 vs. 410 min, respectively), and the time to definitive diagnosis is significantly shorter (6.3 vs. 16.8 h, respectively) (11,12). The only disadvantage to helical CT scanning is the two-to threefold larger radiation dose compared with the 3-film IVP (8,9,13).…”
Section: Discussionmentioning
confidence: 99%
“…As shown by Patel et al [17] a protocol with initial US and KUB is cheaper and delivers a lower radiation dose to the patient, although reaching a diagnostic conclusion takes longer than immediate UHCT. On the other hand, UHCT (as the initial examination) reduces the time of diagnosis and the overall management cost.…”
Section: Discussionmentioning
confidence: 99%
“…Immediate UHCT alone has the advantage of reducing the time of diagnosis and the overall management cost [17]. The combination of CT and with KUB and US has the advantage of being cheaper and delivering a lower dose, although reaching a diagnostic conclusion may take longer.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, NESCT has displaced IVU to become the investigation of choice for acute flank pain in many institutions across North America, [5][6]9,11 Europe, 14 and Australasia. 13,15 Our impression from local experience, together with discussion with colleagues in various regions across the country, is that this is not generally the case in the UK. The aim of this study was to survey UK and Irish urologists to determine their current practice in investigation of acute flank pain and their reasons for the choice, with particular regard to the use of IVU or NESCT.…”
Section: Introductionmentioning
confidence: 99%